Reproductive Performance of Mares Fed Dietary Zearalenone - Vance, Carrie K.; King, E. Heath; Bowers, Susan D.; Ryan, Peter L.; Walters, Kevin; Shappell, Nancy W. (Frontiers in Veterinary Science, 2019)
It is known that zearalenone (ZON) interacts directly with estrogen receptors, and its in vivo effects on reproduction have been well documented in several species. In contrast, reports of ZON’s impact on horse reproduction are conflicting and inconclusive, some studies confounded by the presence of mycotoxins such as deoxynivalenol in the feed. This study assesses the effect of chronic consumption of zearalenone on reproduction in cycling mares fed >95% pure ZON (0, 2 or 8 mg/da; n=7 mares/treatment) for three estrous cycles, followed by artificial insemination, through 16 days of pregnancy. Animals were on ZON treatment for between 70 and 121 days (average 84) depending on individual cycle patterns. ZON-induced changes in serum concentration of estradiol (E2) and progesterone (P4), and total estrogenicity were measured using RIAs and the E-screen assay, respectively. Effects on reproductive physiology and pregnancy were monitored by ultrasound and clinical parameters. No significant changes were found in reproductive hormone levels of E2, or P4 for mares on ZON treatments compared to controls, although there was a significant (P < 0.01) increase in P4 levels across Cycle number in High ZON (8 mg/da) treated mares. There was also an increasing trend in the interovulatory interval in the High ZON treatment group. The overall estrogenicity was similar across treatments and over time, not differing from controls or between ZON treatment groups. Adverse uterine and ovarian effects were also not observed, but pregnancy rates were mixed with only 4 of 7 mares on Low ZON becoming pregnant, and only 3 maintaining pregnancy and fetal heartbeat by Day 30, compared to 5 of 6 control mares and all 7 mares on High ZON. Because reproductive efficiency and hormone concentrations are highly variable across individuals, this study did not demonstrate that ZON at 2 or 8 mg/da was detrimental to mares’ reproduction. Yet, inferring that ZON treatments were completely without effect is also not appropriate, as the absence of measurable significant differences could be attributed to the limited sample size. Most importantly, there were no extreme signs of toxicology, in contrast to previous reports when ZON was fed at these “doses”.